Perusing of Organizational Culture Effects on E-Mail Communication. (2016) - Madanchian, Mitra; Taherdoost, Hamed
Abstract: Today most business communications and transactions are conducted via Computer Mediated Communication (CMC) and email is the most familiar type of CMC. In fact, email plays a crucial role in establishing and maintaining business relationships, both within a company and with external contacts. This study investigates organizational culture and its effects on E-Mail communication adopting Hofstede's theory of culture and organization and as a case study, an Iranian Organization has been selected. A questionnaire was distributed within selected organization's employee along with three important variables to come across effects of culture into organization. Finally, the findings clarified the influence of organizational culture on email communication in the selected Iranian organization by drawing on the theory adopted in this study.